Early Lumbar Nerve Root Deficit After Three Column Osteotomy for Fixed Sagittal Plane Deformities in Adults - RUSTAGI, TARUSH (Int J Spine Surg, 2018)
BACKGROUND: Three-column osteotomy is an effective means of correcting fixed sagittal plane deformities. Deformity correction surgeries may be associated with early postoperative neurological deficits often presenting as palsies involving the lumbar roots. The objective was to retrospectively assess a subset of our series of adult deformity correction surgeries and analyze neurological deficits and associated patient and surgical factors. METHODS: Hospital records of 17 patients from a single center were examined. Inclusion criterion were adults (>18 years) who underwent a 3-column osteotomy (pedicle subtraction osteotomy) at the lumbar level for fixed sagittal plane deformities including positive sagittal balance, flat back syndrome, and posttraumatic kyphosis. These also included cases with associated degenerative lumbar scoliosis. Patients were divided in 2 groups: Group 1 with lumbar root deficit and Group 2 with no deficits. We examined the surgical details of the osteotomy, complications during surgery, and observed if the magnitude of correction in the sagittal or coronal plane bore any influence on the nerve deficit. RESULTS: All 17 patients had a single-level resection except 1 patient who had 2-level osteotomy; 23.5% (4 of 17) developed nerve deficit. Nerve deficit presented as bilateral foot drop (1); unilateral extensor hallucis longus (EHL) weakness (2); and unilateral quadriceps weakness (1). The patient with quadriceps weakness partially recovered to functional strength. Two patients with EHL weakness fully recovered; however, the patient with bilateral foot drop did not improve. L5-S1 interbody fusion was done in 3 of 4 cases in Group 1 and 4 of 13 cases in Group 2. CONCLUSIONS: Nerve deficits after 3-column corrective osteotomies occurred in 23% cases. All but 1 case had significant improvement. Most nerve palsies are neuropraxia and unilateral and tend to recover. L5 weakness appears most common after high lumbar osteotomies. Significant correction of scoliosis at the osteotomy level (>50%) may be a reason for nerve palsy.